Antimicrobial Activity of Novel Deep Eutectic Solvents - Noor Akbar; Naveed Ahmed Khan; Taleb Ibrahim; Mustafa Khamis; Amir Sada Khan; Ahmad M. Alharbi; Hasan Alfahemi; Ruqaiyyah Siddiqui (MDPI AG, 2023)
Herein, we utilized several deep eutectic solvents (DES) that were based on hydrogen donors and hydrogen acceptors for their antibacterial application. These DES were tested for their bactericidal activities against Gram-positive (Streptococcus pyogenes, Bacillus cereus, Streptococcus pneumoniae, and methicillin-resistant Staphylococcus aureus) and Gram-negative (Escherichia coli K1, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Serratia marcescens) bacteria. Using lactate dehydrogenase assays, DES were evaluated for their cytopathic effects towards human cells. Results from antibacterial tests revealed that DES prepared from the combination of methyl-trioctylammonium chloride and glycerol (DES-4) and DES prepared form methyl-trioctylammonium chloride and fructose (DES-11) at a 2 µL dose showed broad-spectrum antibacterial behavior and had the highest bactericidal activity. Moreover, DES-4 showed 40% and 68% antibacterial activity against P. aeruginosa and E. coli K1, respectively. Similarly, DES-11 eliminated 65% and 61% E. coli K1 and P. aeruginosa, respectively. Among Gram-positive bacteria, DES-4 showed important antibacterial activity, inhibiting 75% of B. cereus and 51% of S. pneumoniae. Likewise, DES-11 depicted 70% B. cereus and 50% S. pneumoniae bactericidal effects. Finally, the DES showed limited cytotoxic properties against human cell lines with the exception of the DES prepared from Methyltrioctylammonium chloride and Citric acid (DES-10), which had 88% cytotoxic effects. These findings suggest that DES depict potent antibacterial efficacies and cause minimal damage to human cells. It can be concluded that the selected DES in this study could be utilized as valuable and novel antibacterial drugs against bacterial infections. In future work, the mechanisms for bactericides and the cytotoxicity effects of these DES will be investigated.